Efficient Distribution of a Novel Zirconium-89 Labeled Anti-cd20 Antibody Following Subcutaneous and Intravenous Administration in Control and Experimental Autoimmune Encephalomyelitis-Variant Mice - Migotto, Mary-Anne; Mardon, Karine; Orian, Jacqueline; Weckbecker, Gisbert; Kneuer, Rainer; Bhalla, Rajiv; Reutens, David C. (Frontiers in Immunology, 2019)
Objective: To investigate the imaging and biodistribution of a novel zirconium-89 (89Zr)-labeled mouse anti-CD20 monoclonal antibody (mAb) in control and experimental autoimmune encephalomyelitis (EAE) mice following subcutaneous (s.c.) and intravenous (i.v.) administration. Background: Anti-CD20-mediated B-cell depletion using mAbs is a promising therapy for multiple sclerosis. Recombinant human myelin oligodendrocyte glycoprotein (rhMOG)-induced EAE involves B-cell-mediated inflammation and demyelination in mice. Design/Methods: C57BL/6J mice (n=39) were EAE-induced using rhMOG. On Day 14 post EAE induction, 89Zr-labeled-anti-CD20 mAb was injected in control and EAE mice in the right lower flank (s.c.) or tail vein (i.v.). Positron emission tomography/computed tomography (PET/CT) imaging and gamma counting (ex vivo) were performed on Days 1, 3 and 7 to quantify tracer accumulation in the major organs, lymphatics, and central nervous system (CNS). A preliminary study was conducted in healthy mice to elucidate full and early kinetics of the tracer that were subsequently applied in the EAE and control mice study. Results: 89Zr-labeled anti-CD20 mAb was effectively absorbed from s.c. and i.v. injection sites and distributed to all major organs in the EAE and control mice. There was a good correlation between in vivo PET/CT data and ex vivo quantification of biodistribution of the tracer. From gamma counting studies, initial tracer uptake within the lymphatic system was found to be higher in the draining lymph nodes (inguinal or subiliac and sciatic) following s.c. versus i.v. administration; within the CNS a significantly higher tracer uptake was observed at 24 hours in the cerebellum, cerebrum and thoracic spinal cord (p<0.05 for all) following s.c. versus i.v. administration. Conclusions: The preclinical data suggest that initial tracer uptake was significantly higher in the draining lymph nodes (subiliac and sciatic) and parts of CNS (the cerebellum and cerebrum) when administered s.c. compared with i.v in EAE mice.